Training companies tapped into the AI world / Nur Zania Azurin Abdullah Sani - Abdullah Sani, Nur Zania Azurin (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
In my opinion, the rise of Midjourney AI has revolutionized the way we create images and videos, and its applications extend far beyond the realm of art and design. As a result, companies like Karyative Ventures and Midjourney Mahir Malaysia are now conducting training classes on Midjourney AI to provide a valuable insights to brand owners, photographers, and graphic designers who want to stay ahead of the curve and take advantage of this exciting technology. Midjourney AI training can help individuals and organizations save time and resources by automating repetitive tasks and optimizing workflows. This is especially valuable for smaller businesses or independent creators who may not have access to the same level of resources as larger organizations. By learning how to use Midjourney AI effectively, they can work more efficiently and effectively and achieve results that otherwise would have been difficult or impossible to achieve through traditional methods alone.